Organic Chemistry Laboratory Techniques - Nichols, Lisa; Open Textbook Library (Open Textbook Library, 2016)
This resource was created by Lisa Nichols (chemistry faculty at Butte Community College in Northern California) as a result of an academic sabbatical leave in the Fall-2015 to Spring 2016 term. The target audience are undergraduate students in organic chemistry. In this resource you will find theory and procedures on the main organic lab techniques (chromatography, crystallization, extraction, distillation) as well as general concepts on how to set up and heat apparatuses (see the Table of Contents tab for a more complete listing of topics). All procedures are accompanied by step-by-step pictures, and graphics are heavily utilized throughout the resource.
Chapter 1: General Techniques -- Chapter 2: Chromatography -- Chapter 3: Crystallization -- Chapter 4: Extraction -- Chapter 5: Distillation -- Chapter 6: Miscellaneous Techniques -- Chapter 7: Technique Summaries
In English.
Description based on online resource
Keywords: Science -- Textbooks; Chemistry -- Textbooks